Ovarian epithelial tumors Study of 70 cases.: Value factor analysis forecast. Therapeutic results
The author analyses 10 cases o/ epithelial tumors of the ovary whose average age was 54; and were stadified as follows: S /, 23 cases (33%), S 11, 17 cases (24%